A method for the cost optimization of industrial electrical routings. Issue 5 (3rd September 2018) - Castorani, Vincenzo; Cicconi, Paolo; Mandolini, Marco; Vita, Alessio; Germani, Michele
ABSTRACT: The cost reduction is one of the most spread strategy adopted by companies for guaranteeing profits in a competitive market. This paper presents an approach for the cost optimization of industrial electrical routings. The proposed optimization process consists of two levels: the arrangement of the cables within the cable trays and the 3D routing of the cable trays for connecting the modules of a product. The arrangement of the power and signal cables and the selection of the cable trays are carried out considering specific configuration rules. A genetic algorithm, coupled with the Hightower's algorithm, is used to solve the routing optimization problem. The proposed cost functions consider the raw materials and manufacturing/assembly operations. The optimization process has been used for optimizing a portion of the electric cable harness of a 43 MWe power plant with a size of 44 × 20 meters, and a total of 40, 60 kilometers of cables. The optimization process let to a cost saving of about 15% compared to the design carried out with the traditional approach. Abbreviations: CTs : cable trays; CUi : hourly rate for the installation phase [€/hour]; CUrmtk : hourly rate for the k-th cost center used for transforming a semi-finished component [€/hour]; Cut : hourly rate for the test phase [€/hour]; CUtray : unitary cost of a cable tray [€]; DOE : design of experiment; GA : genetic algorithm [€]; Ic : installation cost [€]; If : installation factor [-]; PAc : cost for the preliminary analysis [€]; PAcp : percentage used for calculating the cost of the preliminary analysis [%]; RMc : cost of the raw material and relative transformation operations [€]; RMcci : cost of the i-th commercial component [€]; RMoc : percentage of the overhead costs related to the management of the raw material [%]; RMsc _ scrapsj : cost of the scraps for the j-th semi-finished component [€]; RMscj : cost of the j-th semi-finished component [€]; RMtc : cost for transforming semi-finished components [€]; Tcl : commercial length of a straight cable tray [meter]; Tii, j : standard installation time for the i-th or j-th component [hour]; Tl : linear distance between two points of the wiring system that need to be connected [meter]; Trmtk : time for the k-th operation for transforming a semi-finished component [hour]; Ttk : standard test time for the k-th skid of the electrical system [hour]. GRAPHICAL ABSTRACT: